2022
DOI: 10.1002/ece3.9029
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific coprophagia by wild red foxes:DNAmetabarcoding reveals a potentially widespread form of commensalism among animals

Abstract: Vertebrate animals are known to consume other species' faeces, yet the role of such coprophagy in species dynamics remains unknown, not least due to the methodological challenges of documenting it. In a large‐scale metabarcoding study of red fox and pine marten scats, we document a high occurrence of domestic dog DNA in red fox scats and investigate if it can be attributed to interspecific coprophagia. We tested whether experimental artifacts or other sources of DNA could account for dog DNA, regressed dog occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…[39,191,192]) or simply because they are avoiding dingoes [193]. As well as potentially representing scavenging, traces of predator hair could indicate coprophagy for nutritional gain, as has been reported for foxes [194,195] and modern dogs [196,197].…”
Section: Discussionmentioning
confidence: 99%
“…[39,191,192]) or simply because they are avoiding dingoes [193]. As well as potentially representing scavenging, traces of predator hair could indicate coprophagy for nutritional gain, as has been reported for foxes [194,195] and modern dogs [196,197].…”
Section: Discussionmentioning
confidence: 99%
“…The examination of red fox scats in Scotland found a curiously high percentage of domestic dog (C. l. familiaris) DNA. Researchers linked this finding to coprophagia, which may help to sustain red fox populations when their natural prey base fluctuates (Waggershauser et al, 2022). Coyotes (C. latrans) in New York City were expected to have human food in their diet, but DNA metabarcoding showed that domestic chicken (Gallus gallus), presumably intended for human consumption, comprised nearly half of dietary counts (Henger et al, 2022).…”
Section: Application Of Dna Metabarcoding For Species In Other Parts ...mentioning
confidence: 99%
“…Coprophagy is well‐known in leporids (Hirakawa, 2001 ), but the practice has also been observed in a wide range of other organisms, from insects (Körner et al, 2016 ), fish (Rempel et al, 2022 ), rodents (Kenagy & Hoyt, 1979 ), and canids (Waggershauser et al, 2022 ), to large herbivores such as African elephant (Leggett, 2004 ), and non‐human primates (Krief et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%